MICRO AND MACRO SKILLS OF READING COMPREHENSION ACQUIRED BY EFL STUDENTS - Ida Bagus Nyoman Mantra; Ida Ayu Made Sri Widiastuti; Anak Agung Istri Yudhi Pramawati (Denpasar Institute, 2020)
Reading comprehension is a very important language skill to support our life in many aspects. In education sectors, reading comprehension is an ability for the students to continually develop their skills in various subjects. Consequently, assessment of students' reading comprehension is absolutely essential to be conducted to systematically collect information and making inferences about the ability of a student or the quality of the learning process. This study revealed that students' reading comprehension is at a sufficient level and students still experienced some challenges in reading comprehension. This study implies that more intensive reading comprehension activities should be carried out and better learning strategies should be employed by the teachers in teaching reading comprehension.